Management accounting in the Malaysian public sector: Analysing the adoption of financial and risk analysis - A.K Siti Nabiha; Noriza Mohd Jamal; M. Rozaidy (Institut Perakaunan Negara, 2023)
Purpose: This paper aimed to analyse the introduction of financial analysis and risk management for internal decision-making in the Malaysian public sector and determine the limitations/ gaps as well as areas for improvement. Design/ Methodology/ Approach: The paper was based on the analysis of documents, government circulars and guidelines pertaining to financial statement analysis and risk management, including interviews with officers at two ministries. Findings: Policy and guidelines were established for financial analysis and risk management in the Malaysian public sector. However, given the complexities and unique context of each ministry, there is a need for clearer and more context-specific guidelines regarding financial and risk analysis. It is also crucial that the conducted financial and risk analyses are relevant and meet the specific needs of public sector entities. The usefulness of information relies on a comprehensive understanding of the context and types of decision needed. Therefore, fostering collaboration and engagement between the management accountant unit and other key units within a ministry is crucial to conduct an effective financial and risk analysis. Originality/ Value: This study offered insights into the financial and risk analysis reporting framework and its implementation in the Malaysian public sector